The investigation of Moscow state academy of fine chemical technology excellent student's life principles (in accordance with the public opinion poll) - A. A. Derevyanchenco; S. U. Ivanov (Тонкие химические технологии)
Value orientations, professional aspirations, life principles and problems of a number of excellent MITHT students connected with the studying and up-bringing process and the system of further job placement are exposed.